Key value drivers throughout business life cycle - Saller, Andriy (2019)
This research master’s thesis adapts the concept of business life cycle as the basis for valuation ofany company. Main characteristics, valuation approaches and methods for start-up, high-growth,mature and declining companies are discussed in order identify key drivers determining the firmvalue. Case study valuations are conducted for Qover, Netflix, Microsoft, and General Electric toprovide empirical evidence for the impact of key value drivers at each stage of business life cycle.